The Relationship Between Duration of Mechanical Ventilator Use and Mortality in the Intensive Care Unit (ICU) at PMI Hospital Bogor in 2023 - Yulianti, Sri (Westscience Press, 2023)
Mechanical ventilator is a breathing support device that helps patients with respiratory failure. Use of mechanical ventilator for more than 48 hours causing complications that could increase mortality in patients. Knowing the association between duration of mechanical ventilator use and mortality in ICU can help reduce the factors that cause patient's mortality in ICU. This study used an analytic observational method with a cross sectional approach. Subjects were 97 medical record data with simple random technique then processed using SPSS. This study used secondary data with medical records of patients in ICU with use of mechanical ventilator according to sample's inclusion and exclusion. The analysis used is chi-square. The results showed that the majority of subjects were >65 years old (37.1%), male (60.8%). Non surgical patients (56.7%), the most common primary diagnoses were ICH (17.5%), CKD (10.3%), CHF (6.2%), and peritonitis (6.2%), duration of mechanical ventilator use ≥48 hours (61.9%) and patient died (83.5%). Bivariate analysis results showed there was no association between duration of mechanical ventilator use and mortality (p = 0.734). There is no association between duration of mechanical ventilator use with mortality in the ICU RS PMI Bogor in 2023. Further research is needed to determine other factors that can affect mortality in ICU other than the duration of mechanical ventilator use.